Faktor-Faktor Yang Berhubungan Dengan Partisipasi Remaja Dalam Mengikuti Posyandu Remaja Di Desa Karya Jaya : Factors Associated with Adolescent Participation in Attending Youth Posyandu in Karya Jaya Village - Rohmayani, Siti (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: The Integrated Healthcare Center for Teenagers is a form of Community-Based Health Effort (UKBM) that is managed and organized by and with the community including the teenagers for the implementation of health development to empower the community and improve convenience in obtaining health services for teenagers.  Methods: The design of this study is a quantitative method with a cross-sectional research design, and sampling techniques by random sampling. Data analysis consists of univariate and bivariate analysis using chi-square assays.  Results: There is a relationship between knowledge and the participation of adolescents following Integrated Healthcare Center statistical tests with p-value (0,015) < α (0,05). There is a relationship between the distance of residence support and the participation of adolescents visiting The Integrated Healthcare Center, statistical tests with p-value (0,009) < α (0,05). There is a relationship between family support and the participation of adolescents visiting the Integrated Healthcare Center statistical tests with statistical values p-value (0,001) < α (0,05). There was no relationship between peer support and the participation of adolescents visiting the Integrated Healthcare Center statistical tests with statistical values of p-value (0,517) > α (0,05).  Discussion: This research is expected for the Youth Integrated Healthcare Center to always conduct surveys so that Integrated Healthcare Center services can run well.